Cortical and Thalamic Excitation Mediate the Multiphasic Responses of Striatal Cholinergic Interneurons to Motivationally Salient Stimuli - Doig, N; Magill, P; Apicella, P; Bolam, J; Sharott, A (Society for Neuroscience, 2014)
Cholinergic interneurons are key components of striatal microcircuits. In primates, tonically active neurons (putative cholinergic interneurons) exhibit multiphasic responses to motivationally salient stimuli that mirror those of midbrain dopamine neurons and together these two systems mediate reward-related learning in basal ganglia circuits. Here, we addressed the potential contribution of cortical and thalamic excitatory inputs to the characteristic multiphasic responses of cholinergic interneurons in vivo. We first recorded and labeled individual cholinergic interneurons in anesthetized rats. Electron microscopic analyses of these labeled neurons demonstrated that an individual interneuron could form synapses with cortical and, more commonly, thalamic afferents. Single-pulse electrical stimulation of ipsilateral frontal cortex led to robust short-latency (<20 ms) interneuron spiking, indicating monosynaptic connectivity, but firing probability progressively decreased during high-frequency pulse trains. In contrast, single-pulse thalamic stimulation led to weak short-latency spiking, but firing probability increased during pulse trains. After initial excitation from cortex or thalamus, interneurons displayed a "pause" in firing, followed by a "rebound" increase in firing rate. Across all stimulation protocols, the number of spikes in the initial excitation correlated positively with pause duration and negatively with rebound magnitude. The magnitude of the initial excitation, therefore, partly determined the profile of later components of multiphasic responses. Upon examining the responses of tonically active neurons in behaving primates, we found that these correlations held true for unit responses to a reward-predicting stimulus, but not to the reward alone, delivered outside of any task. We conclude that excitatory inputs determine, at least in part, the multiphasic responses of cholinergic interneurons under specific behavioral conditions.